-
Notifications
You must be signed in to change notification settings - Fork 0
/
Homework3.tex
230 lines (187 loc) · 7.56 KB
/
Homework3.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
\documentclass[paper=letter, fontsize=11pt]{scrartcl} % Letter paper and 11pt font size
\usepackage{amstext, amsmath, amssymb}
\usepackage[T1]{fontenc} % Use 8-bit encoding that has 256 glyphs
\usepackage[english]{babel} % English language/hyphenation
\usepackage{amsmath,amsfonts,amsthm} % Math packages
\usepackage{fancyhdr} % Custom headers and footers
\pagestyle{fancyplain} % Makes all pages in the document conform to the custom headers and footers
\fancyhead{} % No page header - if you want one, create it in the same way as the footers below
\fancyfoot[L]{} % Empty left footer
\fancyfoot[C]{} % Empty center footer
\fancyfoot[R]{\thepage} % Page numbering for right footer
\renewcommand{\headrulewidth}{0pt} % Remove header underlines
\renewcommand{\footrulewidth}{0pt} % Remove footer underlines
\setlength{\headheight}{13.6pt} % Customize the height of the header
\setlength\parindent{0pt} % Removes all indentation from paragraphs
%----------------------------------------------------------------------------------------
% TITLE SECTION
%----------------------------------------------------------------------------------------
\newcommand{\horrule}[1]{\rule{\linewidth}{#1}} % Create horizontal rule command with 1 argument of height
\title{
\normalfont \normalsize
\textsc{San Francisco State University} \\ [25pt]
\horrule{0.5pt} \\[0.4cm] % Thin top horizontal rule
\huge MATH 301 Assignment 3 \\ % The assignment title
\horrule{2pt} \\[0.5cm] % Thick bottom horizontal rule
}
\author{Omar Sandoval}
\date{\normalsize\today}
\begin{document}
\maketitle
%----------------------------------------------------------------------------------------
% PROBLEM 14
%----------------------------------------------------------------------------------------
\textbf{14.} Prove Bernoulli's inequality
\begin{align*}
(1+x)^n \ge 1 + nx
\end{align*}
for all non-negative integers n and real numbers $x > -1$. \\
--\\
Proof by Induction\\
I) Base Case \\
\begin{align*}
\text{For } n &= 0, \\
(1 + x)^0 &\ge 1 + 0 \cdot x \\
1 &\ge 1 \\
&\text{Thus, base case holds.}
\end{align*}
II) Inductive Step \\
Suppose for all non-negative integer \textit{k} and real number $x > -1$, $P(k) \Rightarrow P(k+1).$ \\
$P(k): (1 + x)^k \ge 1 + kx.$ \\
$P(k+1): (1 + x)^{k+1} \ge 1 + (k + 1)x.$ \\
Consider $P(k+1)$: \\
NTS: $(1 + x)^{k+1} \ge 1 + (k + 1)x.$. \\
Notice $x > -1 = 1 + x > 0$ \\
Also, $k \ge 0$ and $x^2 \ge 0$ $\rightarrow$ $xk^2 \ge 0$. \\
By the inductive definition, $(1 + x)^{k+1} = (1 + x)(1 + x)^k.$ \\
By the inductive hypothesis, $(1 + x)^{k+1} \ge 1 + kx \rightarrow (1 + x)(1 + x)^k.$ \\
$ = (1 + x)^{k+1} \ge (1 + kx)(1 + x)$ \\
$ = 1 + x + kx + kx^2$ \\
$ = 1 + (k + 1)x + kx^2 \ge 1 + (k + 1)x + 0$ \\
$ = 1 + (k + 1)x$, since $kx^2 \ge 0$.\\
So, $(1 + x)^{k+1} \ge 1 + (k+1)x$.\\
\\
Finally, through induction on $n$, $(1 + x)^n \ge 1 + nx$ for all non-negative $n$ and real numbers $x > -1$.
\\
\\
%----------------------------------------------------------------------------------------
% PROBLEM 15
%----------------------------------------------------------------------------------------
\textbf{15.} For which non-negative integer values of \textit{n} is $n! \ge 3^n$? \\
-- \\
The proposition holds for $n = 0$ and integers which are greater than or equal to 7. \\
When $n = 0$, $n! = 0! = 1$, also, $3^n = 3^0 = 1$. \\
Clearly, $1 \ge 1$. \\
Proof by Induction for $n \ge 7$. \\
I) Base Case
$n = 7$ \\
$n! = 7! = 5040$ \\
$3^n = 3^7 = 2187$ \\
$ 5040 \ge 2187$ \\
II) Inductive Step \\
Suppose $P(k) \Rightarrow P(k + 1).$ \\
$P(k): k! \ge 3^k$ for some integer $k \ge 7$. \\
$P(k+1): (k+1)! \ge 3^{k+1}$ \\
$3k! \ge 3 \cdot 3k$ \\
$(k + 1)! = (k + 1)k!$ by our inductive definition. \\
$(7 + 1)k! = 8k! \ge 3k! \ge 3 \cdot 3^k = 3^{k+1}$ \\
Finally, by induction on $n$, $n! \ge 3^n$ for all integers $n \ge 7$.
\\
%----------------------------------------------------------------------------------------
% PROBLEM 16
%----------------------------------------------------------------------------------------
\textbf{16.} Prove by induction on \textit{n} that
\begin{align*}
\sum_{i=1}^{n} \frac{1}{i(i+1)} = \frac{n}{n+1}
\end{align*}
for all positive integers \textit{n}. \\
--\\
Proof by Induction \\
I)Base Case \\
For $n = 1$, \\
$\sum_{i=1}^1 \frac{1}{i(i+1)} \ \frac{1}{1(1+1} = \frac{1}{2}$
and, $\frac{n}{n+1} = \frac{1}{1+1} \frac{1}{2}$ \\
Clearly, base case holds.\\
II) Inductive Step \\
Suppose $P(k) \Rightarrow P(k + 1)$. \\
$P(k): \sum_{i=1}^{k} \frac{1}{i(i+1)} = \frac{k}{k+1}$ \\
$P(k+1): \sum_{i=1}^{k+1} \frac{1}{i(i+1)} = \frac{k+1}{k+2}$ \\
By the inductive definition and hypothesis, \\
$\sum_{i=1}^{k+1} \dfrac{1}{i(i+1)} = \sum_{i=1}^{k}
\dfrac{1}{i(i+1)} + \dfrac{1}{(k+1)(k+2)}$ \\
$= \dfrac{k}{k+1}+\dfrac{1}{(k+1)(k+2)}$ \\
$= \dfrac{k^2 + 2k + 1}{(k+1)(k+2)}$ \\
$= \dfrac{(k+1)^2}{(k+1)(k+2)}$ \\
$= \dfrac{k+1}{k+2}$ \\
Finally, by induction on $n$, $\sum_{i=1}^n \dfrac{1}{i(i+1)} = \dfrac{n}{n+1}$
%----------------------------------------------------------------------------------------
% PROBLEM 17
%----------------------------------------------------------------------------------------
\textbf{17.} For a positive integer \textit{n} the number $a_n$ is defined inductively by
\begin{align*}
a_1 &= 1, \\
a_{k+1} &= \frac{6a_k + 5}{a_k + 2}, \text{ for } k \text{ a positive integer.} \\
\end{align*}
-- \\
(i) $a_n > 0$ \\
I) Base Case \\
For $n = 1$, \\
$a_n = a_1 = 1 > 0$ \\
Base case holds. \\
II) Inductive Step\\
Suppose $P(k) \Rightarrow P(k+1)$ \\
$P(k): a_k > 0$ \\
$P(k+1): a_{k+1} = \dfrac{6a_k + 5}{a_k + 2} > 0$.\\
Using our inductive hypothesis, \\
$a_k > 0 \rightarrow a_k + 2 > 0$ and $a_k > 0 \rightarrow
2a_k > a_k \rightarrow 6a_k > a_k \rightarrow 6a_k + 5 > a_k + 2 > 0.$. \\
So, $\dfrac{6a_k + 5}{a_k + 2} > 1 > 0 \rightarrow \dfrac{6a_k + 5}{a_k + 2} > 0$. \\
Finally, by induction on $n$, $a_n < 5$ for all positive integers $n$.
(ii) $a_n < 5$. \\
I) Base Case
For $n = 1$, \\
$a_n = a_1 = 1 < 5$. \\
Base case holds.
II) Inductive Step \\
Suppose $P(k) \Rightarrow P(k+1)$.\\
$P(k): a_k < 5$ \\
$P(k+1): a_{k+1} = \dfrac{6a_k + 5}{a_k + 2} < 5$. \\
Using our inductive hypothesis, \\
$a_k < 5 \rightarrow 6a_k < 5a_k + 5 \rightarrow 6a_k + 5 < 5a_k + 10$ \\
$= 5(a_k + 2) \rightarrow 6a_k + 5 < 5(a_k + 2)$.
So, $\dfrac{6a_k + 5}{a_k + 2} < 5$.
Finally, by induction on $n$, $a_n < 5$ for all positive integers $n$.
\\
%----------------------------------------------------------------------------------------
% PROBLEM 19
%----------------------------------------------------------------------------------------
\textbf{19.} Prove that
\begin{align*}
\prod_{i=1}^n (1 - \frac{1}{i^2}) = \frac{n + 1}{2n}
\end{align*} \\
for integers $n \ge 2$.\\
-- \\
I) Base Case \\
For $n = 2$ \\
$\prod\limits_{i=1}^2 (1 - \dfrac{1}{i^2}) = 1 - \dfrac{1}{2^2})$
$= \dfrac{3}{4}$ \\
$ \dfrac{n+1}{2n} = \dfrac{2+1}{2(2)} = \dfrac{3}{4} $.\\
Base case holds. \\
II) Inductive Step \\
Suppose that $P(k) \Rightarrow P(k+1)$\\
$P(k): \prod\limits_{i=1}^k (1 - \dfrac{1}{i^2}) = \dfrac{k + 1}{2k}$ \\
$P(k+1): \prod\limits_{i=1}^{k+1} (1 - \dfrac{1}{i^2})
= \dfrac{(k+1) + 1}{2(k+1)} = \dfrac{k + 2}{2k + 2}$ \\
\begin{align*}
\prod_{i=1}^{k+1} (1 - \frac{1}{i^2}) &=
[\prod_{i=1}^k (1- \dfrac{1}{i^2})] \cdot (1 - \dfrac{1}{(k+1)^2}) \\
&= \dfrac{k+1}{2k} \cdot (1 - \dfrac{1}{(k+1)^2}) \\
&= \dfrac{(k+1)[(k+1)^2 - 1]}{2k(k+1)^2} \\
&= \dfrac{(k+1)^2 - 1}{2k(k+1)} \\
&= \dfrac{k^2 + 2k}{2k(k+1)} \\
&= \dfrac{k(k+2)}{2k(k+1)} \\
&= \dfrac{k+2}{2k+2}
\end{align*}
Finally, by induction on n, $\prod\limits_{i=1}^n (1 - \frac{1}{i^2})
= \frac{n + 1}{2n}$, for all integers $n \ge 2$.
\end{document}